Analisis Perhitungan Harga Pokok Produksi Roti dengan Menggunakan Metode Full Costing pada UMKM San Roti - Wahyu Bagus Putra; Yulinartati; Elok Fitriya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In Indonesia, many companies or MSMEs do not use proper financial records, especially in calculating the cost of production. Even though this calculation is really needed so that there are no errors in calculating the cost of production. The method used in this research is the Full Costing method because this method is required to include all costs incurred in the production process, including variable overhead costs and fixed overhead. It is from this background that this research was conducted with the title